2014
DOI: 10.1177/0893318914538561
|View full text |Cite
|
Sign up to set email alerts
|

Two Paths Diverged

Abstract: This research examines the antecedents that motivate and prepare social entrepreneurs to begin social ventures. Drawing from in-depth interviews with 20 social entrepreneurs, this research reveals that there are two paths to social entrepreneurship: the activist path and the business path. Both activist and business social entrepreneurs were motivated by a family legacy or a transformative early adulthood experience as the moral basis for forming a social venture, and both suggested that prior work experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…This is also in line with how prior experience facilitates the generation of awareness and knowledge of the social aspects for opportunity development of social ventures (Corner & Ho, 2010), as well as with the importance of prior education and volunteering experience in forming a social venture (Shumate et al, 2014). Nevertheless, the effect of this variable is comparably weak.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This is also in line with how prior experience facilitates the generation of awareness and knowledge of the social aspects for opportunity development of social ventures (Corner & Ho, 2010), as well as with the importance of prior education and volunteering experience in forming a social venture (Shumate et al, 2014). Nevertheless, the effect of this variable is comparably weak.…”
Section: Discussionmentioning
confidence: 68%
“…Prior experiences in self-employment and entrepreneurial education can be a trigger and a guide for potential entrepreneurs because such experiences nurture and encourage them to start up an enterprise (Keat, Selvarajah, & Meyer, 2011). Furthermore, such experiences seem to enable social entrepreneurs to understand what works and what does not work before engaging in a new venture, identify role models, and develop confidence in establishing an enterprise (Shumate, Atouba, Cooper, & Pilny, 2014). Khuong and An (2016) determined the positive association between prior entrepreneurial experiences and entrepreneurial intentions, demonstrating how entrepreneurship training and education might shape students' future professions.…”
Section: Ijep -International Journal Of Educational Psychology 6(3) 307mentioning
confidence: 99%
“…Entrepreneurs may experience shortage of social provision, may be involved in a traumatic event, may endure poverty during their childhood, or may be initiated into a family tradition of volunteering (Stephan and Drencheva, 2017). These can be described as transformative early adulthood experiences (Shumate et al, 2014) that may lead to social engagement. Entrepreneurs who experienced a problematic situation in their youth may want to address a certain issue now that they are adults.…”
Section: Triggering Empathy By a Critical Life Eventmentioning
confidence: 99%
“…Chandra and Shang (2017) found that motivations can be traced back to a social entrepreneur's past. An important "life event" can trigger a traditional entrepreneur to focus on a social cause (Shumate et al, 2014). Furthermore, unique personal circumstances are suggested as a reason to start a social enterprise (Saebi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cope and Watts (2000, p. 114) add that a critical incident is "essentially an emotional event" that arouses intense feelings and involvement with critical experiences. In a qualitative study on the causes of social entrepreneurship, social entrepreneurs pointed to significant events that provided direct exposure to circumstances (for example, visiting developing countries, living in inner cities) and that differed significantly from their familiar environments (Shumate et al 2014). Those critical events not only "triggered a major change in the trajectory of their life", but also "directly informed the type of social venture they formed" (Shumate et al 2014, pp.…”
Section: Prior Experience Critical Incidents and Their Influence Onmentioning
confidence: 99%